An original meaning of Si Tou Timou Tumou Tou in post-independence war Indonesia: A first-hand experience of Sam Ratulangi’s oldest daughter - Alva Supit; Emilia A. Pangalila-Ratulangie (Tumou Tou, 2022)
Sitou timou tumou tou (ST4) has been a well-recognized philosophy adopted by the Minahasan people. During its development, it has become even more popular within the scope of education. ST4 was said to be first mentioned by the Minahasan national hero, Sam Ratulangi. The interpretations of ST4 have been abundant, mostly reciting the educational aspect: “a man lives to make other men humans.” However, a direct historical record on when and in what situation ST4 was first mentioned by Sam Ratulangi is not well known by the academia and general public. In fact, there has not been any written authoritative source about this manner. In this auto-narrative historical research, the authors took advantage of the direct experiential account of the oldest daughter of Sam Ratulangi (the second author) when ST4 was first said by Sam Ratulangi himself. This has revealed a novel, but rather the original intention of Sam Ratulangi when he first mentioned ST4 in the context of post-war Indonesia: “a man lives to live as a real man.”